2020
DOI: 10.1002/ange.201908593
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Nitroalkylation for Selective Protein Modification and Peptide Stapling

Abstract: Nitroalkanes react specifically with aldehydes, providing rapid, stable, and chemoselective protein bioconjugation. These nitroalkylated proteins mimic key post‐translational modifications (PTMs) of proteins and can be used to understand the role of these PTMs in cellular processes. Demonstrated here is the substrate scope of this bioconjugation by attaching a variety of tags, such as NMR tags, fluorescent tags, affinity tags, and alkyne tags, to proteins. The structure and enzymatic activity of modified prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…By stapling two glutamic acids rapidly through a reaction between nitroalkanes and aldehydes, Raj et al demonstrated the efficiency and selectivity of nitroalkanes in bioconjugation reactions. 31 These compounds can be easily incorporated into various proteins using chemical and biochemical methods (Scheme 4).…”
Section: Glu-glu Staplingmentioning
confidence: 99%
“…By stapling two glutamic acids rapidly through a reaction between nitroalkanes and aldehydes, Raj et al demonstrated the efficiency and selectivity of nitroalkanes in bioconjugation reactions. 31 These compounds can be easily incorporated into various proteins using chemical and biochemical methods (Scheme 4).…”
Section: Glu-glu Staplingmentioning
confidence: 99%
“…In addition to the above progress, manipulation and understanding the biological function of PTM protein isoform can be achieved through PTM site‐specific installation of covalent PTM modification on wild type proteins 184 . Currently, chemical methods 185,186 or genetic methods have been successfully developed to incorporate many different PTM modifications including phosphorylation, 187,188 glycosylation, 189,190 ubiquitination, lipidation, acetylation, 191 methylation, 192 ADP‐ribosylation, sulfation, 193,194 SUMOylation, 195 nitro alkylation, 196 and oxidation of cysteines 197 . There are three types of chemical biology methods allowing covalent modifications, especially for histone, namely chemical mutagenesis, protein semisynthesis, and genetic code expansion 198 .…”
Section: Targeting Ptm Protein Isoforms In Drug Designmentioning
confidence: 99%
“…In particular, α-oxo aldehydes, 32 which can now be routinely incorporated site-selectively at both N-terminal and internal positions within proteins, 33−35 offer great potential for the development of novel bioconjugations due to their uniquely electrophilic nature. Although recent studies have shown these α-oxo aldehydes are reactive in C−C ligations, 36,37 much of the work in this field has been focused on the synthesis of heteroatom linked thiazolidine, 38 oxime, and hydrazone bioconjugates from aldehyde precursors. 39−41 These transformations have principally employed anilines as organocatalysts, leading to large increases in reaction rates at neutral pH or below.…”
Section: ■ Introductionmentioning
confidence: 99%